ACCIDENTS ON BOARD AN AIRCRAFT: GOALS AND OBJECTIVES OF THE INVESTIGATION - Sopilko, Iryna M.; Bezzubov, Dmytro O. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: to determine the features of ensuring the investigation of an accident on board an aircraft. Methods: analysis and synthesis of options for the occurrence of aircraft accidents on board an aircraft, the interpretation method has identified a system to counter the development of negative scenarios. Results: the legal aspects of the concept of an accident are identified, the statistics of aircraft accidents are analyzed. Discussion: a proposal to include this issue on the agenda of international organizations.